1989
DOI: 10.1111/j.1365-2362.1989.tb00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Modifications induced by diabetes on the physicochemical and functional properties of erythrocyte plasma membrane

Abstract: Increasing evidence suggests that in experimental diabetes an impairment in Na+,K+-ATPase activity plays a central role in the pathophysiology of diabetic complications, while only a few data are available with regard to human subjects. We studied the erythrocyte membrane Na+,K+-ATPase activity and membrane fluidity in insulin-dependent and non-insulin-dependent diabetic subjects. A significant decrease in the enzyme activity and in fluorescence polarization values was found in both groups compared with normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 40 publications
(18 reference statements)
2
12
1
Order By: Relevance
“…The patients studied by Hill et al [10] had a similar duration of diabetes but were younger (9-19 years) and some patients had microvascular disease. The patients studied by Testa et al [5], Mazzanti et al [6], Juhan-Vague et al [7] and Rahmani-Jourdheuil et al [8] however, all had IDDM of similar duration and age to those patients in the present study, but some of the patients in these previous studies had diabetic complications. The results in the present study demonstrate that the presence of diabetic complications could affect membrane fluidity as those patients with diabetic nephropathy had lower membrane fluidity compared to their uncomplicated counterparts although this was not different when compared to normal control subjects.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The patients studied by Hill et al [10] had a similar duration of diabetes but were younger (9-19 years) and some patients had microvascular disease. The patients studied by Testa et al [5], Mazzanti et al [6], Juhan-Vague et al [7] and Rahmani-Jourdheuil et al [8] however, all had IDDM of similar duration and age to those patients in the present study, but some of the patients in these previous studies had diabetic complications. The results in the present study demonstrate that the presence of diabetic complications could affect membrane fluidity as those patients with diabetic nephropathy had lower membrane fluidity compared to their uncomplicated counterparts although this was not different when compared to normal control subjects.…”
Section: Discussioncontrasting
confidence: 51%
“…As anisotropy and fluidity are inversely related, this indicates increased fluidity in the deep hydrophobic regions of the erythrocyte membrane. This has been reported in previous studies [5][6][7][8], although others have also reported normal [9,10] or lower fluidity [11][12][13] as assessed by DPH in diabetes. The reason for these differences is not entirely clear.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…It has been reported that erythrocytes from diabetic patients have a higher intracellular Na + concentration (4). Several mechanisms may account for the observed Ca 2+ increase.…”
Section: Discussionmentioning
confidence: 91%
“…In Siena consensus paper; a grade A was assigned to calcium dobesilat, MPFF, and O-(betahydroxyethyl) rutosides (HR)-oxerutins, a grade B to escin and ruscus extracts and a grade C to the remaining VADS (21). Recently published Society for Vascular Surgery and the American Venous Forum guideline suggested that diosmin, hesperidin, rutoside, micronized purified flavonoid fraction or horse chestnut seed extract (escin) must be used in addition to compression therapy for chronic venous disease (Grade 2, Evidence level B) (22). Table 1.…”
Section: Introductionmentioning
confidence: 99%